Analysis of Factors of Utilization of Homegarden As an Effort to Meet Family Nutrition in Tambakrejo Village, Jombang Regency - Yusron Rosyadi; Anggi Indah Yuliana; Mochamad Chumaidi (AGARICUS: Advances Agriculture Science & Farming, 2021)
The homegarden is a place or land around the yard of the house with clear boundaries, planted with one or various types of plants and still has an emotional relationship with the owner or is functional with the house in question. This study aimed to determined the factors of using homegarden in an effort to meet family nutrition in Tambakrejo Village, Jombang Regency. This type of research is analytic and the research design is cross sectional. The sample in the study was 96 respondents. The results of the study obtained that there was no relationship between education and the use of homegarden in an effort to meet family nutrition in Tambakrejo Village, Jombang Regency with a significance value = 0.285%. There is a relationship between knowledge and the use of homegarden in an effort to increase family nutrition in Tambakrejo Village, Jombang Regency with a significance value = 0.000%. There is a relationship between the number of family members and the use of homegarden in an effort to increase family nutrition in Tambakrejo Village, Jombang Regency, the significance value = 0.000%. There is a relationship between income and the use of homegarden in an effort to increase family nutrition in Tambakrejo Village, Jombang Regency with a significance value = 0.011%. There is a relationship between behavior and the use of homegarden in an effort to increase family nutrition in Tambakrejo Village, Jombang Regency, the significance value = 0.000%. There is a relationship between attitude and the use of homegarden in an effort to increase family nutrition in Tambakrejo Village, Jombang Regency, the significance value = 0.000%. It is hoped that the people of Tambakrejo Village will further optimize the use of homegarden in order to create environmentally friendly and healthy